2012
DOI: 10.1242/jcs.101048
|View full text |Cite
|
Sign up to set email alerts
|

Ckip-1 Regulates Mammalian and Zebrafish Myoblast Fusion

Abstract: SummaryMultinucleated muscle fibres arise by fusion of precursor cells called myoblasts. We previously showed that CKIP-1 ectopic expression in C2C12 myoblasts increased cell fusion. In this work, we report that CKIP-1 depletion drastically impairs C2C12 myoblast fusion in vitro and in vivo during zebrafish muscle development. Within developing fast-twich myotome, Ckip-1 localises at the periphery of fast precursor cells, closed to the plasma membrane. Unlike wild-type myoblasts that form spatially arrayed mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…These include the Mbc homolog DOCK1 and DOCK5 in zebrafish and mouse [42,43], the small GTPase Rac1 in zebrafish and mouse [42,44], and N-WASP in mouse [45], suggesting that vertebrate myoblast fusion may involve similar actin cytoskeletal rearrangements as in Drosophila , although the subcellular localization and the potential sidedness of these proteins have not been investigated. In addition, Baas et al have identified a role for Casein kinase 2 interacting protein-1 (CKIP-1), a phospholipids binding protein, in fast muscle development in zebrafish embryos [46]. Morpholino knockdown of ckip-1 impairs fast muscle myoblast fusion and elongation without affecting muscle differentiation.…”
Section: The Second Step Toward Myoblast Fusion – Enhancing Cell Membmentioning
confidence: 99%
“…These include the Mbc homolog DOCK1 and DOCK5 in zebrafish and mouse [42,43], the small GTPase Rac1 in zebrafish and mouse [42,44], and N-WASP in mouse [45], suggesting that vertebrate myoblast fusion may involve similar actin cytoskeletal rearrangements as in Drosophila , although the subcellular localization and the potential sidedness of these proteins have not been investigated. In addition, Baas et al have identified a role for Casein kinase 2 interacting protein-1 (CKIP-1), a phospholipids binding protein, in fast muscle development in zebrafish embryos [46]. Morpholino knockdown of ckip-1 impairs fast muscle myoblast fusion and elongation without affecting muscle differentiation.…”
Section: The Second Step Toward Myoblast Fusion – Enhancing Cell Membmentioning
confidence: 99%
“…Tropomyosins are essential actin-stabilizing proteins in the lamella that act in concert with the actin-polymerizing proteins at the leading edge, including the Wiskott-Aldrich syndrome proteins (WASP) and the actin-related proteins (ARP)2/3 complex, to drive both normal and metastatic cell migration (Bugyi and Carlier, 2010;Gross, 2014). With respect to myogenesis, the WASP and ARP2/3 protein complexes are essential for myoblast fusion (Baas et al, 2012;Berger et al, 2008;Richardson et al, 2007), and WASP proteins promote myoblast migration (Kawamura et al, 2004). Although the mechanisms that direct myotube elongation are thought to mimic those of migratory cells (Bongiovanni et al, 2012), the role of Tropomyosin during myotube elongation has not been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Its function in muscle is largely unknown, but differential expression has been found in rodent cerebellum and spinal cord with exercise (Caetano-Anollés et al, 2016;Perreau et al, 2005) . ID3 is a transcriptional regulator that inhibits skeletal muscle differentiation and promotes muscle precursor cells proliferation (Baas et al, 2012;Liu et al, 2002;Wu and Lim, 2005) . Its expression is negatively correlated with skeletal muscle power in older individuals (Buford et al, 2011) and we also observe a small, but significant association with age.…”
Section: Long-term Training Induces Extracellular Matrix Reorganizatimentioning
confidence: 99%
“…has been found to be a regulator of myoblast elongation and fusion through its interaction with Arp2/3 (Baas et al, 2012) .…”
Section: Long-term Training Induces Extracellular Matrix Reorganizatimentioning
confidence: 99%